Efeitos do factoring sobre a liquidez de uma empresa de comércio de plásticos no Distrito de Tarapoto - Shupingahua Tapullima , Viviana (2022)
The general objective of the study has been to determine the effect of factoring on the liquidity of a commercial plastics company in the District of Tarapoto. Applied research, descriptive scope, non-experimental design - cross-sectional. The sample consisted of a plastics trading company, whose instruments applied were the interview guide and the registration form. The results were: Factoring is made up of its credit management activities (Analysis of the modality, credit sales and accounts receivable), financial debt (debt capacity, rates and commissions). The organization has had an annual negotiation of S / 450,000 minus the factoring that amounts to 15% S / 67,500 with a monthly rate of 7.5% and administrative expenses for banking S / 10,000, finally, it received the accumulated amount of S / 382,500. The liquidity analysis showed a working capital of -S / 34,857.61 (negative), general liquidity for 0.93, acid test for 0.60, defensive test for 0.05. Conclusion: The effect of factoring on liquidity is significant, because, if the company had not used this, current liquidity would have shown a decrease of 0.33 cents, likewise in the acid test it would have shown a decrease of 0.14 cents.